Building a Patient Safety Toolkit for use in general practice. Issue 9 (September 2016) - Bell, Brian G; Spencer, Rachel; Marsden, Kate; Perryman, Katherine; Campbell, Stephen M; Avery, Anthony J
Despite 340 000 000 primary care consultations annually in the UK, most of the literature on patient safety has focused on hospital-based services. To improve safety in primary care settings, we must know what methods, tools and indicators are available to measure and monitor patient safety. In collaboration with patient safety experts at the University of Dundee, we were able to identify a number of existing tools, and many of these were adopted for use in the Patient Safety Toolkit.